Nepal’s Foreign Alignments Amidst Competing Global Ideologies - Paudel, Santosh Kumar (International Research Journal of MMC, 2026)
Nepal’s location between China and India, and engagement with Western powers has made its foreign policy complex in global ideological competition between liberalism and communism. Though Nepal upholds non-alignment policy, its diplomatic engagements show a pragmatic balancing strategy shaped by external pressures and domestic considerations. This study examines how Nepal’s foreign policy reflects influence of liberal and communist ideologies, and explores challenges of balancing relations with China, India, and Western countries. It also analyzes role of domestic political actors and institutions in shaping foreign policy. The research adopts a qualitative, interpretive case-study design grounded in small-state diplomacy and asymmetric international relations. Secondary data were collected from books, peer-reviewed journal articles, studies on Nepal’s foreign policy and small-state behavior. Analysis also draws upon primary political documents, official government policy statements, constitutional provisions, and speeches by influential political leaders. Data were analyzed using qualitative thematic and interpretive content analysis. The findings indicate that Nepal pursues a pragmatic hedging strategy rather than strict ideological alignment, balancing relations with China, India, and West to maximize strategic autonomy. Domestic political actors and institutions significantly shape foreign policy decisions, where regime security and nationalist considerations take precedence over ideological consistency. The study concludes that Nepal’s foreign policy is best understood as a dynamic negotiation between domestic political imperatives and external geopolitical pressures. These findings contribute to the literature on small-state diplomacy by demonstrating how ideological competition and domestic political dynamics jointly influence the foreign policy behavior of states operating within asymmetric regional power structures.